Pelatihan Green Skills bagi Pengelola Wisata untuk Mendukung Pariwisata Berkelanjutan di Desa Budo - Rondonuwu, Dianne O; Fonny Sangari; Dimas E. Permana; Benny Irwan Towoliu (Jurnal Ragam Pengabdian, 2025)
The practices of sustainable tourism principles in business units managed by Bumdesa in Budo Village are still far from green tourism. Examples of green skills practices in tourism include: Use of Renewable Energy: Utilizing solar, wind, or water energy to meet the energy needs of accommodation and tourism operations. Waste Management: Implementing recycling programs, waste reduction, and responsible waste management. Use of Environmentally Friendly Materials: Building accommodation and tourism facilities using environmentally friendly materials. Environmentally friendly transportation: providing clean public transportation, such as bicycles or electric vehicles, for tourists. Training methods: opening or escorting, core activities and material delivery, closing and evaluation. The results show that participants were enthusiastic about the training activities, as seen from the average participant satisfaction evaluation, and were committed to implementing the planned projects.